Boundary Value Problems Governed by Superdiffusion in the Right Angle: Existence and Regularity - Ramzet Dzhafarov; Nataliya Vasylyeva (Journal of Mathematics)
For α∈(1,2), we analyze a stationary superdiffusion equation in the right angle in the unknown u=u(x1,x2): Dx1αu+Dx2αu=f(x1,x2), where Dxα is the Caputo fractional derivative. The classical solvability in the weighted fractional Hölder classes of the associated boundary problems is addressed.